Jernets tvang! Om ressourceudnyttelsens paradoksale natur i Harald Kiddes Jærnet - Nyboe, Jacob Ølgaard (Passage - Tidsskrift for litteratur og kritik, 2026)
The Force of the Iron: On the Paradoxical Nature of Resource Exploitation in Harald Kidde’s Jærnet This article aims to establish Harald Kidde’s novel Jærnet (1918) as and overlooked classic and modernist pioneer work. Through a new materialistic approach, I demonstrate how iron is presented as a non-human actant with whom both the society and the psychology of its individuals is highly intertwined. The novel, thus, in a sophisticated manner explores conflicts and paradoxes of our relationship to natural resources, highly relevant for contemporary society.